Strategies Used in Writing Theses and Dissertations at Yemeni Universities - Mansoor, Maged Salem Yeslam; Al-Marrani, Yahya Mohammed Ali (International Journal of Language and Literary Studies, 2024)
This study aims to identify the strategies used in writing theses and dissertations at Yemen universities. A quantitative research method was employed to collect data from 100 MA and Ph.D. students, 21 supervisors, and 19 examiners through a questionnaire and analyze it using SPSS descriptive statistics. The results showed that postgraduate students used different strategies, such as selecting an achievable topic, early selection of study topic in my master or Ph.D. programs, consulting my supervisor for advice, citing previous studies to support my ideas, and revising the draft of my thesis or dissertation before submitting it to the examiners. The results also revealed no significant differences between males and females in the utilization of writing strategies in any of the dimensions. Additionally, there were no significant variations found between master’s and Ph.D. level students regarding the strategies used in writing their theses and dissertations. The researcher recommended the need for a comprehensive study to explore postgraduate students’ writing strategies, examining differences across disciplines and universities, gender and qualification impacts, and the effectiveness of specific strategies. The role of supervisors and examiners in promoting effective writing strategies should also be evaluated, with suggestions for enhancing their support.